DISTRIBUTION OF SUBSURFACE QUATERNARY SEDIMENT IN SOUTH BINTAN ISLAND WATERS AS A POTENTIAL HEAVY MINERAL PLACER OR RARE EARTH ELEMENT DEPOSIT BASED ON SEISMIC INTERPRETATION - Muhammad Zulfikar; Nazar Nurdin; Noor Cahyo Dwi Aryanto; Ildrem Syafri; Budi Muljana; Andi Agus Nur (BULLETIN OF THE MARINE GEOLOGY, 2021)
Bintan Island is one of the areas traversed by the Southeast Asian granitoid belt which is known to have the potential for heavy mineral placer deposits. Due to the dwindling presence of heavy mineral placer deposits in land areas, it is necessary to look for the potential presence of heavy mineral placer deposits in water areas. Searching for placer heavy mineral deposits accomodation in these waters requires subsurface mapping.The method used in this subsurface mapping is a single channel seismic method with a total of 179 lines in the direction of northeast – southwest and west – east. The results of this seismic recording are then interpreted the boundaries of the seismic facies unit and distributed using the kriging method. Furthermore, the thickness calculates by using the assumption velocity 1600 m/s.Based on the facies unit boundaries that have been interpreted, the quaternary sediments that formed in the study area are divided into 2 types of units, namely: Unit 2 which is estimated to be fluvial – transitional sediment, and Unit 1 which is estimated to be transitional sediment – shallow sea. There is also a difference in thickness patterns in these two units, where unit 2 shows a pattern of sediment thickening that resembles a paleochannel trending northeast – southwest, while unit 1 is relatively uniform.From the results of this study, it can be said that the area that has potential for heavy mineral placer  deposits is in the west - center of the southern waters of Bintan Island. Where the potential for heavy mineral placer deposits should be in the paleochannel deposits that are part of Unit 2.